A novel 2L-Y DC-DC converter topologies for high conversion ratio renewable application - Maroti P.K.; Padmanaban S.; Bhaskar M.S.; Blaabjerg F.; Ramachandaramurthy V.K.; Siano P.; Fedak V. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric inverters; Energy conversion; MATLAB; Topology; Compact structures; Converter topologies; Internal resistance; L-Y converter; Renewable energies; Single stage converters; Voltage gain; X-Y Converter; DC-DC converters